2021
DOI: 10.2196/23934
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Medical Record–Based Case Phenotyping for the Charlson Conditions: Scoping Review

Abstract: Background Electronic medical records (EMRs) contain large amounts of rich clinical information. Developing EMR-based case definitions, also known as EMR phenotyping, is an active area of research that has implications for epidemiology, clinical care, and health services research. Objective This review aims to describe and assess the present landscape of EMR-based case phenotyping for the Charlson conditions. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 276 publications
2
20
0
Order By: Relevance
“…Consistent with other literature regarding complex phenotypes, we found that reliance on diagnostic codes can vary in accuracy depending on the jurisdiction [ 14 , 27 ]. System-level and jurisdictional differences in diagnostic coding requirements reduced the sensitivity of case definition 1 in the CPCSSN reference set.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Consistent with other literature regarding complex phenotypes, we found that reliance on diagnostic codes can vary in accuracy depending on the jurisdiction [ 14 , 27 ]. System-level and jurisdictional differences in diagnostic coding requirements reduced the sensitivity of case definition 1 in the CPCSSN reference set.…”
Section: Discussionsupporting
confidence: 89%
“…Case definition 4 supplemented specific diagnostic codes with NLP of short diagnostic text fields in the EMR to identify patients with PTSD. Similar to other works, we found that combining structured EMR data and unstructured free text significantly improved diagnostic capture in our pan-Canadian data set yielding higher performance [ 7 , 15 , 20 , 27 ]. However, we did not ascertain additional benefit from using free-text encounter notes when compared to short diagnostic text fields that are more widely available.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study has several limitations. First, we identified MCI patients and AD onsets using ICD codes (Supplementary Tables 2) which were provided by physicians and validated in 47, 48 , yet there might be a certain level of inaccuracy due to mis- and under-diagnosis or the lack of clinical details in EHRs or claims 38, 49 . Information contained in clinical notes will be explored in the future through natural language processing to complement the structured codes.…”
Section: Discussionmentioning
confidence: 99%